Manipulation of immunodominant dengue virus E protein epitopes reduces potential antibody-dependent enhancement - Hughes, Holly R (BioMed Central, 2012)
BACKGROUND: Dengue viruses (DENV) are the most important arboviruses of humans and cause significant disease. Infection with DENV elicits antibody responses to the envelope glycoprotein, predominantly against immunodominant, cross-reactive, weakly-neutralizing epitopes. These weakly-neutralizing antibodies are implicated in enhancing infection via Fcγ receptor bearing cells and can lead to increased viral loads that are associated with severe disease. Here we describe results from the development and testing of cross-reactivity reduced DENV-2 DNA vaccine candidates that contain substitutions in immunodominant B cell epitopes of the fusion peptide and domain III of the envelope protein. RESULTS: Cross-reactivity reduced and wild-type vaccine candidates were similarly immunogenic in outbred mice and elicited high levels of neutralizing antibody, however mice immunized with cross-reactivity reduced vaccines produced significantly reduced levels of immunodominant cross-reactive antibodies. Sera from mice immunized with wild-type, fusion peptide-, or domain III- substitution containing vaccines enhanced heterologous DENV infection in vitro, unlike sera from mice immunized with a vaccine containing a combination of both fusion peptide and domain III substitutions. Passive transfer of immune sera from mice immunized with fusion peptide and domain III substitutions also reduced the development of severe DENV disease in AG129 mice when compared to mice receiving wild type immune sera. CONCLUSIONS: Reducing cross-reactivity in the envelope glycoprotein of DENV may be an approach to improve the quality of the anti-DENV immune response.